Food waste in school canteens: A reference methodology for large-scale studies. (1st May 2018) - Boschini, Matteo; Falasconi, Luca; Giordano, Claudia; Alboni, Fabrizio
Abstract: Food waste reduction is increasingly seen as a main way to improve sustainability of food systems and efficiency of resource use. The provision of reliable data is a prior element to provide proper intervention strategies. Numerous studies carried out to date did not allow to a generalization of results obtained and the lack of standard methods limited data comparability. The most appropriate method for quantifying food waste in large-scale studies has not yet been established for this specific sector. The aim of the present study is to devise a reference methodology for quantifying food waste in school canteens suitable for large-scale studies, time-saving and able to provide reliable and comparable data. Initial servings, plate waste and non-served food are weighed with an electronic scale. Data are separated by dish type and aggregated at school level, whereas results are adjusted to provide comparable data. The data collection process (weighing and data recording) is directly performed by food service personnel, teachers and students. A pre-test in a primary school and a pilot study in four primary schools were conducted with the external support of a single researcher which coordinated different schools at the same time reducing the need for external support. The methodology demonstrated that the data accuracy of weighing methods is not necessarily associated with an increase in time and costs. Highlights: Large-sample studies are crucial to provide national and comparable data on food waste. A methodology to quantify FW in school canteens in large-scale studies is presented. An average of 576 students were daily monitored under the supervision of a researcher. An average of 107 g of avoidable plate waste was produced daily by each participant.